Discovery of TCMs and derivatives against the main protease of SARS-CoV-2 via high throughput screening, ADMET analysis, and inhibition assay in vitro - Qi, Xinyu; Li, Binglin; Omarini, Alejandra B.; Gand, Martin; Zhang, Xiaoli; Wang, Jiao (Journal of molecular structure, 2022)
The rapidly evolving Coronavirus Disease 2019 (COVID-19) pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread worldwide with thousands of deaths and infected cases. For the identification of effective treatments against this disease, the main protease (Mpro) of SARS‑CoV‑2 was found to be an attractive drug target, as it played a central role in viral replication and transcription. Here, we report the results of high-throughput molecular docking with 1,045,468 ligands’ structures from 116 kinds of traditional Chinese medicine (TCM). Subsequently, 465 promising candidates were obtained, showing high binding affinities. The dynamic simulation, ADMET (absorption, distribution, metabolism, excretion and toxicity) and drug-likeness properties were further analyzed the screened docking results. Basing on these simulation results, 23 kinds of Chinese herbal extracts were employed to study their inhibitory activity for Mpro of SARS‑CoV‑2. Plants extracts from Forsythiae Fructus, Radix Puerariae, Radix astragali, Anemarrhenae Rhizoma showed acceptable inhibitory efficiencies, which were over 70%. The best candidate was Anemarrhenae Rhizoma, reaching 78.9%.
Gesehen am 19.08.2022